New species of Augochlora (Oxystoglossella) Eickwort (Hymenoptera; Apoidea) from Northeastern Brazil with an identification key for the region - Lepeco, Anderson; Gonçalves, Rodrigo Barbosa (Zootaxa, 2020)
Within Augochlorini, Augochlora Smith is one of the most speciose genera, with 118 species, and widely distributed groups, occurring from Argentina to Canada. The genus has a remarkable range of social behaviors and nesting substrate preferences. There are two recognized extant subgenera: Augochlora s.s., whose species nest in decaying wood cavities and Oxystoglossella, whose species nest in soil. To date, a single species revision is available for Central Argentina and Uruguay. In the present study we provide a revision of Oxystoglossella species occurring in Northeastern Brazil including the description of three new species: Augochlora bipunctata sp. nov., Augochlora modica sp. nov. and Augochlora tenax sp. nov. Herein Halictus eucnemis Vachal is resurrected from synonymy with Augochlora thalia Smith, and the lectotype of Halictus hemitomes Vachal is presently designated. Augochlora aurinasis is cited for Brazil for the first time. A key to the six species of Oxystoglossella occurring at Northeastern region in Brazil is provided. The three new species are apparently restricted to this region, being one of them probably linked to the Caatinga biome.